INTERPHASE BOUNDARY DIFFUSION OF OXYGEN AND POTASSIUM IN K-FELDSPAR/QUARTZ AGGREGATES - Farver J.R.; Yund R.A. (My University, 1995)
Interphase boundary diffusion rates of oxygen and potassium in fine-grained K-feldspar/quartz aggregates were determined experimentally at 450-700°C and 100 MPa (hydrothermal). The starting materials were hot-pressed and crystallized using equal weights of natural quartz fragments and orthoclase (KA1Si3O8) composition glass. The technique employed isotopic tracers (18O, 41K) in an aqueous solution surrounding the sample, and depth profiling using an ion microprobe (SIMS). From the depth profiles, the product of the average boundary diffusion coefficient (D') and average effective boundary width (δ) was calculated using numerical solutions to the appropriate diffusion equation.Potassium and oxygen profiles measured in the same samples are different, confirming a diffusional transport mechanism. Potassium diffusion in the K-feldspar/quartz aggregate has a greater activation energy than oxygen (218 vs. 75 kJ/mol), and the Arrhenius relations cross at ~600°C. The D' δ values in the K-feldspar/quartz aggregates are about a factor of four greater than both oxygen and potassium D' δ values previously determined in monomineralic K-feldspar aggregates, and a factor of 20-40 greater than oxygen D' δ values in monomineralic quartz aggregates. The Arrhenius relations show the activation energies for both oxygen and potassium are similar for the K-feldspar/quartz and monomineralic K-feldspar aggregates, and significantly lower for oxygen in K-feldspar/quartz versus monomineralic quartz aggregates.